Access recirculation and adequacy of hemodialysis in different types of vascular access - Dr. P. Shrijjaa; Dr. V. N. Narayanan Unni; Dr. Prabhakar M. (International Journal of Medical Research and Review, 2021)
Introduction: Haemodialysis requires recirculation, and it happens when dialysed blood returning through the venous needle re-enters the extracorporeal circuit through the arterial needle, rather than returning to the systemic circulation. Significant recirculation should be expected, when there is an inadequate reduction in the values of urea. During End-Stage Renal Disease (ESRD), adequate dialysis is of utmost importance because it influences the morbidity and mortality of the patients. Methods and materials: The study was carried out in 200 patients who underwent haemodialysis at the dialysis unit in Kalyani kidney care centre, Erode. Patients were actively evaluated from February 2018 till November 2018. Patients were randomized and accordingly 64 patients were enrolled in category I Arteriovenous fistula (AVF), 63 Patients in category II Internal Jugular Catheter (IJC) and category III Femoral Catheter (FC) each and 10 patients in category IV Perm Catheter (PC). Success recirculation was estimated and adequacy of haemodialysis was done virtually. Calculated Kt/V was done in almost all patients. For assessing vascular access recirculation, the technique that was used was urea-based measurement (Two needles with three samples of blood). The recirculation percentage was calculated as(S-A)/(S-V) X100. For assessing the adequacy of haemodialysis, Kt/V was used where K is estimated from (Cbi-Cbo)/ (CbixQb), time duration of dialysis (t) and urea distribution volume (V) is determined from the Watson equations for men and women. Kt/V was also measured with Online Clearance Monitoring (OCM) in Fresenius machine 4000S. Results: The mean access recirculation rate was 6.3+5.1% in those with AVF, while in IJC and FC groups were 6.7+4.5% and 24.4+11.7% respectively. When the two groups were compared, AVF vs FC groups, the difference was statistically significant (p value<0.001) and in IJC vs FC groups, the difference was statistically less significant (p-value <0.001) in both AR% and online Kt/V. Conclusion: An arteriovenous2QQ2 fistula has less access recirculation, when compared to temporary catheters. On the other hand, the femoral catheter has more access recirculation, when compared to the internal jugular catheter. The difference in calculated Kt/V with the three types of vascular access has no statistical significance.